2021
DOI: 10.1093/rb/rbaa056
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating ESD-induced gastric ulcer healing using a pH-responsive polyurethane/small intestinal submucosa hydrogel delivered by endoscopic catheter

Abstract: Endoscopic submucosal dissection (ESD) is the standard treatment for early-stage gastric cancer, but the large post-operative ulcers caused by ESD often lead to serious side effects. Post-ESD mucosal repair materials provide a new option for the treatment of post-ESD ulcers. In this study, we developed a polyurethane/small intestinal submucosa (PU/SIS) hydrogel and investigated its efficacy for accelerating ESD-induced ulcer healing in a canine model. PU/SIS hydrogel possessed great biocompatibility and distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Hydrogels are three-dimensional (3D) polymer networks that hold large amounts of water. This feature allows the encapsulation of active molecules and/or cells and the exchange of nutrients and metabolites. , Among them, injectable and biodegradable hydrogels have gained particular attention because of the minimally invasive treatment manner and have been widely investigated for drug delivery, tissue regeneration, 3D cell culture, , wound healing, postsurgical antiadhesion, and so on. , Thermosensitive hydrogels that undergo sol–gel transitions upon heating are an important class of injectable systems. ,, Their low-viscous sol state at low temperatures facilitates the incorporation of fragile drugs and cells through simple mixing, and this low-temperature loading procedure advantageously protects the activity of fragile agents, such as proteins or polypeptides, and the viability of cells. After the liquid formulation was injected into the body, an in situ gel matrix for drug delivery or cell growth was spontaneously generated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels are three-dimensional (3D) polymer networks that hold large amounts of water. This feature allows the encapsulation of active molecules and/or cells and the exchange of nutrients and metabolites. , Among them, injectable and biodegradable hydrogels have gained particular attention because of the minimally invasive treatment manner and have been widely investigated for drug delivery, tissue regeneration, 3D cell culture, , wound healing, postsurgical antiadhesion, and so on. , Thermosensitive hydrogels that undergo sol–gel transitions upon heating are an important class of injectable systems. ,, Their low-viscous sol state at low temperatures facilitates the incorporation of fragile drugs and cells through simple mixing, and this low-temperature loading procedure advantageously protects the activity of fragile agents, such as proteins or polypeptides, and the viability of cells. After the liquid formulation was injected into the body, an in situ gel matrix for drug delivery or cell growth was spontaneously generated.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among them, injectable and biodegradable hydrogels have gained particular attention because of the minimally invasive treatment manner and have been widely investigated for drug delivery, 8−13 tissue regeneration, 14−16 3D cell culture, 17,18 wound healing, 19 postsurgical antiadhesion, 20 and so on. 19,21 Thermosensitive hydrogels that undergo sol−gel transitions upon heating are an important class of injectable systems. 17,19,22−25 Their low-viscous sol state at low temperatures facilitates the incorporation of fragile drugs and cells through simple mixing, and this low-temperature loading procedure advantageously protects the activity of fragile agents, such as proteins or polypeptides, and the viability of cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a xenogeneic, acellular, biocompatible, biodegradable, and collagen-based scaffold, porcine SIS can enable bladder regeneration without ex vivo cell seeding before the implantation [ [40] , [41] , [42] , [43] ]. The particular biochemical components and excellent mechanical properties have conferred it with appropriate structure and microenvironment not only as a scaffold but also with specific physiological functions suitable for cell adhesion, proliferation, differentiation, and the ultimate tissue regeneration [ 35 , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that this hydrogel had an obvious hemostatic effect in vivo and could promote the generation of type I collagen and blood vessels in the ulcers. Zhao et al [ 49 ] developed a polyurethane intestinal submucosal matrix hydrogel and investigated the effects in a gastric ulcer model of dogs. The results showed that the polyurethane intestinal submucosal matrix hydrogel mainly accelerated wound healing by reducing the inflammatory response and promoting mucosal endothelial cell regeneration.…”
Section: Discussionmentioning
confidence: 99%